2020
DOI: 10.1186/s13046-020-01624-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC9 promotes tumor growth and metastasis via modulating FZD6/Wnt/β-catenin signaling pathway in bladder cancer

Abstract: Background: Accumulating evidence have highlighted the importance of long noncoding RNAs (lncRNAs) in multiple cancers development and progression. Cancer susceptibility candidate 9 (CASC9) is a novel long noncoding RNA and plays important regulatory role in diverse biological processes of cancers. However, the clinical significance and molecular mechanism of CASC9 in bladder cancer is still unknown. Methods: Comprehensive lncRNAs profiling analysis were conducted to identify lncRNAs profile alterations and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
(47 reference statements)
1
31
0
Order By: Relevance
“…The functional assays after RAMS11 downregulation displayed signi cantly reduced CRC cell survival, proliferation, and migration. Our results are in line with previous studies that demonstrated knockdown or knockout of lncRNAs, such as H19, SNHG14, CCAL, and MIR17HG (31)(32)(33)(34)(35), potentially reduced CRC cell proliferation, migration, metastasis, and increased chemo-sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…The functional assays after RAMS11 downregulation displayed signi cantly reduced CRC cell survival, proliferation, and migration. Our results are in line with previous studies that demonstrated knockdown or knockout of lncRNAs, such as H19, SNHG14, CCAL, and MIR17HG (31)(32)(33)(34)(35), potentially reduced CRC cell proliferation, migration, metastasis, and increased chemo-sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanistically, SOX2OT upregulates SOX2 expression by sponging miR-200c 10 . In addition, many lncRNAs such as CASC9 42 , SNHG1 43 , TUG1 44 , and NBAT1 45 are associated with the occurrence and development of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28 In bladder cancer, lncRNA CASC9 acted as a miR-497-5p sponge to up-regulate the expression of FZD6, activate theWnt/β-cateninsignaling pathway, as well as promote the growth and metastasis of bladder cancer. 29 Additional studies have revealed that circFGFR3 participates in the miR-29a-3p/E2F1 axis by inducing the EMT process of ovarian cancer cells and promote the initiation of ovarian cancer. 30 In total, we found 113 DEmRNAs in the established ceRNA network.…”
Section: Discussionmentioning
confidence: 99%